Comparative safety and tolerability of ketamine and esketamine for major depressive disorder: a systematic review and meta-analysis - Guo, Haoning; Tang, Liling; He, Miaoquan; Tang, Wencheng; Liu, Jing; Wu, Silin; Yuan, Shuying; Wang, Jisheng; Tang, Xueli (Frontiers in Pharmacology, 2025)
BackgroundKetamine and esketamine have demonstrated rapid, short-term antidepressant effects in major depressive disorder (MDD), but their relative safety remains unclear. This review aims to update the evidence on the safety of two agents for MDD and indirectly compare their safety and tolerability.MethodWe systematically searched PubMed, PsycINFO, Embase, and Cochrane databases up to 1 May 2025. Eligible studies compared ketamine or esketamine with placebo, active psychotropic agents, or electroconvulsive therapy in adults with MDD.ResultsWe retrieved 5,473 articles, 47 of which met the inclusion criteria. For ketamine versus placebo, both dropout and incidence rates of adverse events (AEs) were statistically significant, with number needed to harm (NNH) values of 12 and 2, respectively. A similar pattern of effect sizes was found for esketamine, but with higher corresponding NNH values. Conversely, neither the meta-analysis nor NNH analyses of the incidence of serious AEs for ketamine and esketamine were statistically significant. A series of AEs like dizziness, dissociation, nausea, vertigo, and vision blurred, with relatively low NNH values, would be more likely to occur in clinical practice and exhibit dose-dependent effects. Moreover, ketamine or esketamine was associated with transient and significant psychiatric side-effects, blood pressure increases, and sedation post-dose. No significant abnormalities were observed in cognitive impairments, laboratory results, bladder symptoms, nasal examination, or addiction-related evaluations for either drug.ConclusionAlthough further promising evidence supports the safety of ketamine and esketamine for MDD, the findings of this study highlight a potential tolerability advantage with esketamine over ketamine for short-term use for MDD. These findings require further validation through direct head-to-head clinical trials comparing these two drugs.Systematic Review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023389486.